1993
DOI: 10.1007/bf01437890
|View full text |Cite
|
Sign up to set email alerts
|

Modified Nilsson model for large sodium clusters

Abstract: Abstract. We propose a modified Nilsson model for spheroidal sodium clusters and investigate the modification of shell structure by deformation for sizes up to N = 850. For spherical clusters, our potential is fitted to the single-particle spectra obtained from microscopically selfconsistent Kohn-Sham calculations using the jellium model and the local density approximation. Employing Strutinsky's shell-correction method, the surface energy of the jetlium model is renormalized to its experimental value. We find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 31 publications
3
52
0
Order By: Relevance
“…the choice of the diffusivity in the definition of V,(z,e), which implies an angular dependence d ( Q ) in our calculations different to, e.g., the definition in [22]. Nevertheless, comparing the results with those of [24] and [52], prolate-to-oblate transitions are kept at about the same particle number in all three models. The absolute value of the deformation strength 6 increases from Na-10 to Na-14.…”
Section: Potential Energy Curvesmentioning
confidence: 83%
See 2 more Smart Citations
“…the choice of the diffusivity in the definition of V,(z,e), which implies an angular dependence d ( Q ) in our calculations different to, e.g., the definition in [22]. Nevertheless, comparing the results with those of [24] and [52], prolate-to-oblate transitions are kept at about the same particle number in all three models. The absolute value of the deformation strength 6 increases from Na-10 to Na-14.…”
Section: Potential Energy Curvesmentioning
confidence: 83%
“…Clemenger introduced a different parameter 6, to describe axial deformations [7], which is related to q by and is only useful for 6 1 4 2 . Another definition (see, e.g., [52]) is…”
Section: Jellium Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…For b = 2 the emerging shell structure is confined to the very low end of the spectrum and to rather small values of λ. where the applicability of the model is no longer certain. For example, in [12] it was found that for large spherical clusters (A = 676 and 832) the energy minima are more pronounced than in the KS calculations, which is an artifact. In other words, while in the axial MHO potential the re-emergence of order and hence shell structure is a fact for large Λ, its physical impact cannot be assessed from this model alone.…”
Section: Quantum Mechanical Treatmentmentioning
confidence: 92%
“…In practical applications the study of the more realistic deformed WS potential is complicated due to the effective occurrence of many multipoles; this is the subject of a future paper. Since the MHO is being used widely for the interpretation of data [1,12,27,28,42] we expand in the present paper the preliminary classical analysis of the MHO potential [41] and demonstrate its connection with quantum-mechanical single particle orbitals. One particular result of the classical analysis is a kind of scaling relationship between energy range and the strength λ of the ( L) 2 term in the MHO potential.…”
Section: Introductionmentioning
confidence: 92%